Assessing the Impacts of COVID-19 on Women Refugees in South Africa - (:unkn) unknown (My University, 2022)
Abstract The global COVID-19 pandemic and subsequent lockdowns and restrictions have had uneven impacts on populations and have deepened many pre-existing inequalities along lines of race, ethnicity, class, gender. Refugees have been shown to be particularly negatively impacted in many countries, with existing structures of violence and insecurity worsened by the immediate consequences of the pandemic through policy responses which largely ignore their needs whether by excluding them from targeted COVID-19 mitigation measures, or by imposing restrictions which directly impact on their well-being. Our research with refugee women in Durban, South Africa, illustrates the ways in which COVID-19 has exacerbated their insecurities and intensified structural violence which renders them vulnerable. More importantly, it seems that the impacts of COVID-19 are not just short term but will deepen the violence and insecurities experienced by these women in the longer term if these are not addressed by government and relevant NGOs and civil society organizations.
Keywords: African Research